2011
DOI: 10.1093/jxb/err304
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and divergence of four kiwifruit SVP-like MADS-box genes suggest distinct roles in kiwifruit bud dormancy and flowering

Abstract: MADS-box genes similar to Arabidopsis SHORT VEGETATIVE PHASE (SVP) have been implicated in the regulation of flowering in annual species and bud dormancy in perennial species. Kiwifruit (Actinidia spp.) are woody perennial vines where bud dormancy and out-growth affect flower development. To determine the role of SVP-like genes in dormancy and flowering of kiwifruit, four MADS-box genes with homology to Arabidopsis SVP, designated SVP1, SVP2, SVP3, and SVP4, have been identified and analysed in kiwifruit and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 56 publications
5
142
0
2
Order By: Relevance
“…In Japanese pear, the expression of the DAM-like gene MADS13 was upregulated towards dormancy establishment and downregulated towards dormancy release . Wu et al (2012) suggested that SVP-like genes in kiwifruit (Actinidia spp.) may have distinct roles in dormancy and flowering.…”
Section: ) Identification Of Dormancy-associated Madsbox Genes In Prmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japanese pear, the expression of the DAM-like gene MADS13 was upregulated towards dormancy establishment and downregulated towards dormancy release . Wu et al (2012) suggested that SVP-like genes in kiwifruit (Actinidia spp.) may have distinct roles in dormancy and flowering.…”
Section: ) Identification Of Dormancy-associated Madsbox Genes In Prmentioning
confidence: 99%
“…For DAM genes, the roles of DAM homologs in fruit tree species other than Prunus should also be clarified since DAM (SVP) homologs seem to be related to the dormancy release of not only peach and Japanese apricot but also Japanese pear , raspberry (Matzzitelli et al, 2007), and kiwifruit (Wu et al, 2012). However, their role has been reported to be less or not significantly related to that of grape (Díaz-Riquelme et al, 2012) and leafy spurge (Horvath et al, 2010).…”
Section: ) Expression Analysis Of Dam Genesmentioning
confidence: 99%
“…Moreover, transgenic Arabidopsis expressing AtSVP orthologs from Actinidia spp. or rice (Oryza sativa) showed leaf-like sepals and secondary flower phenotypes (Trevaskis et al, 2007;Wu et al, 2012). In addition to MTF down-regulation, phytoplasma might induce leafy flower symptom development via upregulated SVP expression.…”
mentioning
confidence: 99%
“…Additionally, it was recently shown that the silencing of PpDAM6 is preceded by changes in the methylation status of H3K27 residues of histones bound to its chromatin (Leida et al 2012), as well as occurs in the silencing of FLC and other genes that regulate vernalization in A. thaliana (Angel et al 2011). Although putative DAM orthologues were identified in pear (Ubi et al 2010;Saito et al 2013), apple (Falavigna et al 2014), raspberry (Mazzitelli et al 2007), kiwifruit (Wu et al 2012), leafy spurge ) and apricot , a complete functional characterization of DAM genes remains to be reported.…”
Section: Molecular Control Of Bud Dormancy Progressionmentioning
confidence: 99%